Probiotics in the comprehensive prevention of respiratory infections in children - S. V. Nikolaeva; D. V. Usenko; Yu. N. Khlypovka; A. V. Gorelov (Лечащий Врач)
Viral infections of the respiratory tract are the most common cause of infectious diseases, especially in children. In most cases, especially when the upper respiratory tract is affected, acute respiratory viral infections are mild to moderate and often stop spontaneously. Pharmacological agents for the treatment or prevention of these infections in children are currently limited. Numerous studies have proven the effectiveness of probiotics in the treatment and prevention of diseases of the gastrointestinal tract, such as infectious and antibiotic-associated diarrhea, traveler's diarrhea, necrotizing enterocolitis, Helicobacter pylori infection, as well as atopic diseases. It is becoming urgent to study the effectiveness of probiotics as prophylactic agents for acute respiratory infections. among children and adults. In vitro data demonstrate that probiotics have strain-specific immunomodulatory effects on immune cells. Probiotics have been shown to be effective in suppressing the replication of various respiratory viruses, including influenza viruses and respiratory syncytial virus. Similar effects have been demonstrated in mice with the ability of probiotics to reduce viral titers in lung tissues and modulate the expression of antiviral and pro-inflammatory genes before and after viral infection. Preclinical studies also show improvement in symptoms in mice, indicating potential clinical benefit. Literature data on the use of probiotics and synbiotics for viral infections of the respiratory tract show that their use is associated with a lower frequency and duration of mild forms of respiratory infection in both children and adults. It is advisable to further conduct research necessary to obtain adequate conclusions about the effectiveness of probiotics and synbiotics in acute respiratory infections.